2022
DOI: 10.1109/access.2022.3160464
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Traffic Data Reconstruction in Large-Scale Internet of Vehicle Systems: A Neural Network Approach

Abstract: Multi-Access Edge Computing (MEC) can reduce transmission costs and provide faster interactive responses in cloud server-centric Internet of Vehicle (IoV) scenarios. However, the resource space of MEC server is limited, and the large amount of data uploaded by RSU may limit the further development of MEC network. Compressed Sensing (CS) proves that for the data with certain internal structure, a complete data set can be reconstructed even if the sampling frequency is lower than the requirements of the sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Qin et al 46 suggested a neural network‐centric framework for traffic data reconstruction intended for a scalable IoV network, named NRTD. The proposed framework modeled the process of the matrix factorization and merged the multilayer perceptron structures to optimize the fitting degree to emulate the time‐variant traffic‐centric data change curve.…”
Section: Analysis Of Data‐centric Approaches In Iovmentioning
confidence: 99%
“…Qin et al 46 suggested a neural network‐centric framework for traffic data reconstruction intended for a scalable IoV network, named NRTD. The proposed framework modeled the process of the matrix factorization and merged the multilayer perceptron structures to optimize the fitting degree to emulate the time‐variant traffic‐centric data change curve.…”
Section: Analysis Of Data‐centric Approaches In Iovmentioning
confidence: 99%